Identification of the yeast strain cystobasidium slooffiae isolated from the cake test sample - A. E. Bazhenova; O. S. Rudenko; M. A. Pesterev; N. A. Shcherbakova; S. Yu. Misteneva (Пищевые системы)
Nowadays, the problem of food safety and quality assurance throughout the product life cycle is topical in the whole world. According to the WHO data, foodborne diseases linked with consumption of unsafe food, including diseases caused by microbial pathogens, are common in many world countries and are still the main cause of morbidity and mortality. Therefore, prevention of the microbiological spoilage of food products is an important task in all food industry sectors. One of the ways for its solution is to carry out investigations to reveal potential sources of microbial contamination of food products including flour confectionery. Cakes are multi-component confectionery products. As a rule, they have the high moisture mass fraction, which conditions the presence of a favorable environment for the development of all types of microorganisms and contributes to the instability of this product type to the effects of environmental conditions during storage. In this study, yeast and mold counts were determined by growing cultures on the solid culture medium (Sabouraud). Pure cultures were isolated by the streak plate method. Stained and unstained microorganisms were examined by the microscopic method. Saccharolytic enzymes of the isolated bacterial cultures were identified using the Hiss’s culture media. Based on the analysis of the ribosomal gene sequence obtained by sequencing the DNA region encoding the ITS-D1/D2 rDNA region, an accurate identification of the strain was performed. The phylogenetic relationship analysis carried out using strains of closely related microorganisms showed that species Cystobasidium slooffiae was the closest relative of the studied strain. The source of Cystobasidium slooffiae was the environment. The detection of this strain indicates violations of the sanitary and hygienic condition of inventory, equipment, industrial premises, including hard-to-reach places, as well as violations of the hygiene rules by personnel; in addition, this indicates the high contamination of raw materials.